EFFORT TO REDUCE ANXIETY LEVELS AMONG MOTHERS USING FEBRILE CONVULSIONS EDUCATIONAL PACKAGE - Siti Rofiqoh; Isyti’aroh Isyti’aroh (Belitung Raya Foundation, Indonesia, 2018)
Background: Parents often experience anxiety when seeing their children having febrile convulsion. It may be due to lack of knowledge about febrile seizure and the way of handling it. Objective: This study aims to analyze the education package of febrile convulsion and its effect on mother’s anxiety. Methods: This was a quasi-experimental study with pretest posttest with control group design. Eighty-one participants were selected, which randomly assigned to be two groups that 41 participants in control group and 40 participants in intervention group. Anxiety was measured using State Anxiety Inventory in Indonesian version. Data were collected from March to Mei, 2017. Data were analyzed using Wilcoxon-test. Results: The results showed that the mean of anxiety level in the intervention group before intervention was 77.40 and decreased to 35.78 after intervention, while the mean of anxiety level in the control group was 68.17 before intervention and decreased slightly to 64.17 after intervention. The p-value of the difference between control and intervention group was 0.001 (<0.05). Conclusion: There was a significant effect of education package about febrile convulsion on mother's anxiety level. It is suggested that febrile convulsion educational package can be used as an alternative therapy to reduce anxiety levels among mothers.